Issues of University Business Incubators Assessment - Khachatryan, Nonna (Bulletin of Yerevan University G: Economics, 2022)
Business incubators, being centers for the generation and maturation of innovative ideas, have different statuses, being state, public, private and university. University business incubators are especially popular in international practice, as by virtue of tradition, universities are the locomotive of research. However, by involving significant financial and human resources, university incubators do not always live up to the expectations of the beneficiaries of their activities, as the generated innovative ideas remain inside the incubators, are not materialized, and find it difficult to find their practical application. In this regard, it is possible to consider the effectiveness of the activities of university incubators in the context of the business ecosystem, which reveals the weak incubation chains of innovative ideas. In this regard, the article proposes a methodology for assessing the effectiveness of the activities of university business incubators based on the expectations of the beneficiaries and their actual achievements. The proposed approach to evaluating the effectiveness of university business incubators makes it possible to analyze not only the actual degree of fulfillment of the beneficiaries’ expectations, but also to observe the nature of business incubators’ activities in the context of the entrepreneurial ecosystem. With such an approach to performance evaluation, it becomes possible to regularly expand and monitor both the circle of business incubators’ beneficiaries and the qualitative composition of their objectives, which results from the requirements of dynamic change of the entrepreneurial environment.